CEU Opening Ceremony, 10th Anniversary (Pesti Vigadó) - Primary Camera I
Recording of the CEU Opening Ceremony for the class of 2001/2002 held at Pesti Vigadó, Concert Hall on October 13, 2001. On this occasion the 10th Anniversary of CEU was also celebrated. The welcome and Opening Remarks are delivered by Stefan Messmann, the Academic Pro-Rector of CEU. Andrej F. Kovaljev who graduated in 1992 is the Alumnus Speaker of the Ceremony and he is followed shortly by Daniela Raiman, an Incoming Student Representative at Legal Studies. Short remarks are then given by the representative of the Faculty, Petr Lom, Associate Professor and PhD Director at Nationalism Studies Program. George Soros, the founder of CEU and the Chairman of the Board of Trustees is introduced by Academic Pro-Rector of CEU to deliver a special announcement – declare the University financially independent and self-supporting. Next to speak is Prof. István Rév (Director of OSA Archivum) who recounts briefly the history of CEU and its developments. President and Rector of CEU, Yehuda Elkana, delivers a short address before the brief musical interlude of the ceremony.